Perancangan Tata Letak Fasilitas Konveksi Roemah Dia Menggunakan Metode SLP - Rosalina, Uki Aulia; Nugeroho, Adik Ahmad Unggul; Perdana, Surya (Universitas Indraprasta PGRI Jakarta, 2025)
The increasing consumer demand for mukena products has an impact on the production process which is required to be fast until the product reaches the consumer. However, the long distance between the production process which is still separated by the location between the warehouse and the production floor causes the ineffectiveness of the production process. To overcome this, Konveksi Roemah Dia must increase production by designing a new production site that has a layout with a minimum distance between production rooms. The purpose of this study is to design a production layout using the Systematic Layout Planning (SLP) method to design the relationship between activities. The results of data processing obtained a floor area between raw materials, cutting tables, sewing machines, embroidery machines, quality control, to finished product warehouses of 43.36 m2. Furthermore, a table of the level of activity proximity relationships was created using the Activity Relationship Chart (ARC) which was summarized into the Worksheet for Activity Relationship Diagram (WARD), then a new layout experiment was made using the Activity Relationship Diagram (ARD), finally a proposed layout was made using the Area Allocation Diagram (AAD) with a U-shaped pattern and a distance of movement between facilities of 13.5 m. The new production floor is carried out in the same place so that there is no waste of distance and time for the material movement process.